2018
DOI: 10.1161/circinterventions.117.005779
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Depth of Radiofrequency-Induced Lesions in Renal Sympathetic Denervation Based on a Fine Histological Sectioning Approach in a Porcine Model

Abstract: Background—Ablation lesion depth caused by radiofrequency-based renal denervation (RDN) was limited to <4 mm in previous animal studies, suggesting that radiofrequency-RDN cannot ablate a substantial percentage of renal sympathetic nerves. We aimed to define the true lesion depth achieved with radiofrequency-RDN using a fine sectioning method and to investigate biophysical parameters that could predict lesion depth.Methods and Results—Radiofrequency was delivered to 87 sites in 14 renal arteries from 9 farm pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…However, the present study showed that electrode temperature in the branch RA (66.2°C) was equivalent to that in main RA (64.2°C), and there was no increase in histopathological arterial damage in the branch RA. The equivalent electrode temperature was likely a result of the automatic control mechanism of the IberisBloom system, which decreases output power when electrode temperature reaches ≥70°C, as shown by the significantly lower terminal output power in the branch RA compared with the main RA . However, impedance was higher when the electrode was located in the branch RA than in the main RA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the present study showed that electrode temperature in the branch RA (66.2°C) was equivalent to that in main RA (64.2°C), and there was no increase in histopathological arterial damage in the branch RA. The equivalent electrode temperature was likely a result of the automatic control mechanism of the IberisBloom system, which decreases output power when electrode temperature reaches ≥70°C, as shown by the significantly lower terminal output power in the branch RA compared with the main RA . However, impedance was higher when the electrode was located in the branch RA than in the main RA.…”
Section: Discussionmentioning
confidence: 99%
“…First, the findings obtained from the normotensive swine may not be applicable to patients with hypertension. However, the normotensive swine is the standard animal model for assessing RDN device safety, because of its anatomical and physiological similarity to humans . Second, because of the small number of animals, adverse findings with a low incidence may have been missed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations